Serum Matrix Metalloproteinase 9 Level, Blood Absolute Neutrophil Count in Correlation with Diffusion Capacity and Exercise Capacity of Stable Chronic Obstructive Pulmonary Disease Patients at Universitas Sebelas Maret Hospital - Lestari, Anggraini Dwi; Apriningsih, Hendrastutik; Reviono, Reviono; Sutanto, Yusup Subagio; Setijadi, Ana Rima (Jurnal Respirologi Indonesia, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality worldwide. Exposure to cigarette smoke activates alveolar macrophages producing neutrophils and proteases such as MMP-9 and NE that damage the extracellular matrix triggering emphysema as well as spill over into the systemic circulation. This study aimed to determine the correlation of serum MMP-9 level and blood absolute neutrophil count with diffusion capacity and exercise capacity of stable COPD patients.Methods: A cross-sectional observational study was conducted in stable COPD patients visiting the pulmonary outpatient clinic of Universitas Sebelas Maret (UNS) Hospital in October 2022. Consecutive sampling was applied for sample collection. We assessed diffusion capacity and exercise capacity with the DLCO method and 6MWT, respectively. We examined serum MMP-9 level and blood absolute neutrophil count. All data were statistically analyzed with SPSS 22.0 and P<0.05 was considered significant.Results: Thirty stable COPD patients were included in the study comprising 19 males (63.3%), and 11 females (36.7%). With a mean age of 61.90±9.99. Serum MMP-9 level did not correlate with either diffusion capacity and blood absolute neutrophil count (P=0.898 and P=0.589, respectively). However, serum MMP-9 level had a significant correlation with exercise capacity (P=0.014). There was no correlation between blood absolute neutrophil count with diffusion capacity and exercise capacity (P=0.0281 and P=0.592, respectively). Diffusion capacity related to exercise capacity (P=0.001).Conclusion: Serum MMP-9 level is not related to diffusion capacity, but it is related to exercise capacity. Blood absolute neutrophil count is not related to diffusion capacity or exercise capacity. Serum MMP-9 level is not associated with blood absolute neutrophil count. Diffusion capacity is related to exercise capacity.